2.56 W Single‐Frequency All‐Fiber Oscillator at 1720 nm. Issue 2 (21st December 2021) - Zhang, Junxiang; Sheng, Quan; Zhang, Lu; Shi, Chaodu; Sun, Shuai; Shi, Wei; Yao, Jianquan
Abstract : The saturable absorption effect of unpumped, rare earth‐doped fiber can be used as a method of achieving single‐frequency operation in fiber lasers. This effect in thulium‐doped fiber is used to achieve single‐frequency operation from an all‐fiber oscillator centered at 1720 nm. The characteristics of the saturable absorption effect are carefully studied and numerous operating regimes are identified wherein the oscillating state and frequency output characteristics of the laser can be manipulated via the injection of auxiliary pump light to the saturable absorber. A record single‐frequency output power of 2.56 W at 1720 nm is obtained; the slope efficiency is 44% and the laser linewidth is 3.3 kHz. The power scaling of the laser is only limited by the available power of the single‐mode 1570 nm pump source. Herein, new insights into methods of generating high‐power, single‐frequency emission from all‐fiber oscillators are offered. Abstract : A Tm 3+ ‐doped fiber ring oscillator which uses the same active fiber as saturable absorber for single‐frequency operation is demonstrated. To overcome the high laser threshold brought by the highly‐absorptive fiber necessary for high‐power single‐frequency operation, an auxiliary pump is utilized to tailor fiber's absorption and frequency‐selection behavior. A record single‐frequency output power of 2.56 W at 1720 nm is obtained.